AB0547 Bone mineral density (bmd) assessment in patients with symptoms suggestive of spondyloarthritis: an accurate tool for diagnosis. (23rd January 2014) - Forien, M.; Molto, A.; Paternotte, S.; Dougados, M.; Roux, C.; Briot, K.
Abstract : Background: Several diseases can mimick spondyloarthritis (SpA) symptoms. Patients may be overdiagnosed in the presence of HLA B27. Patients with spondyloarthritis (SpA) have an increased risk of osteoporosis which can be observed in the early stages of the disease, related to a systemic bone effect of inflammation. Our hypothesis is that BMD is lower in patients with SpA than in patients without this diagnosis. Objectives: The aim of the study was to assess the performances of BMD for the diagnosis of SpA. Methods: Patients who consulted in a tertiary Department of Rheumatology for symptoms suggestive of SpA suspicion between January 2008 and December 2012 were included; exclusion criteria were biological therapies and antiosteoporotic treatment intake. Demographic data, disease duration, activity disease (BASDAI, CRP), presence of HLA B27 were assessed. Bone mineral density (BMD) measurements at lumbar spine and hip were performed using DXA; low BMD was defined by a T score ≤-2 (at at least one site). The diagnosis of confirmed SpA was the one done by the rheumatologist. Comparisons of BMD measurements between patients with or without SpA, and performance of BMD (sensibility, specificity, positive predictive value PPV, negative predictive value NPV and positive likelihood ratio) were performed. Results: Among the 237 patients included (57.8% male, mean age of 40.5±12.0 years), 169 (71%) patients (mean age of 40±12.3 years) had confirmed SpA. Compared to patients without the diagnosis of confirmed SpA (n=44), patients with SpA were more frequently male (64.5% vs 40.9% p=0.005), with positive HLA B27 (80.9% vs 48.8%, p<0.0001) and higher CRP (11.5±15.9mg/l vs 2.8±3.4mg/l, p<0.0001). No differences were found with regard to the disease duration (11.3±9.9 vs 8.2±6.1 y (p=0.163)), BASDAI (39.5±20.9 vs. 48.0±20.7 (p=0.062)) or BASFI (29.3±23.3 vs 27.8±26.1 p=0.586) for the confirmed SpA and non confirmed SpA groups, respectively. Mean lumbar spine BMD was significantly lower in patients with SpA than in patients without (0.99 ±0.16 vs 1.06 ±0.16, p=0.013) without any differences for hip BMD (0.81g/cm 2 vs 0.82±0.13, p=0.25). Low BMD tended to be more frequent in patients with SpA than without (38.2% vs 22.5%, p=0.065). Performances of BMD are in table : low BMD had a high specificity (78% and 90%) and a high PPV (87% and 90%) for low T score at at least one site and at lumbar spine, respectively. Conclusions: In patients having symptoms suggestive of SpA, a low BMD is an additional tool for the diagnosis of SpA. Disclosure of Interest: None Declared